(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article summarizes the results of a systematic study of the influence of the structure and composition of single crystals of the TlInS2 - TlInSe2 system. The equilibrium states of the pseudo binary system TlInS2 - TlInSe2 have been studied by differential-thermal, microstructural and X-ray phase analyses, and the limits of mutual solubility of the initial compounds have been established. It is shown that the grown crystals within (0,3  х  1) on the side of TlInS2 crystallize in the monoclinic system, and on the side of TlInSe2 (0,3  х  1) - in the tetragonal syngony.